Does macro-level general trust influence second language communication?: targeting prefectural capitals - Takehiko Ito; Hideo Ueichi (BMC Research Notes, 2023)
Abstract Objectives This study investigated the macro-level effects of general trust on second language willingness to communicate (WTC) among Japanese individuals residing in 20 prefectural capitals. Previous research has shown the impact of individual-level general trust on WTC; however, macro-level effects have not been explored. Results Multilevel analysis in this research revealed that individual- and prefectural capital-level general trust had a positive influence on WTC in English for Japanese people. Moreover, macro-level effects had a strong predictive power for WTC, thus, highlighting the potential of general trust to facilitate positive connections between people from different cultures.